Attenuation of Native Hyperpolarization-Activated, Cyclic Nucleotide-Gated Channel Function by the Volatile Anesthetic Sevoflurane in Mouse Thalamocortical Relay Neurons - Schwerin, Stefan; Kopp, Claudia; Pircher, Elisabeth; Schneider, Gerhard; Kreuzer, Matthias; Haseneder, Rainer; Kratzer, Stephan (Frontiers in Cellular Neuroscience, 2021)
As thalamocortical relay neurons are ascribed a crucial role in signal propagation and information processing, they have attracted considerable attention as potential targets for anesthetic modulation. In this study, we analyzed the effects of different concentrations of sevoflurane on the excitability of thalamocortical relay neurons and hyperpolarization-activated, cyclic-nucleotide gated (HCN) channels, which play a decisive role in regulating membrane properties and rhythmic oscillatory activity. The effects of sevoflurane on single-cell excitability and native HCN channels were investigated in acutely prepared brain slices from adult wild-type mice with the whole-cell patch-clamp technique, using voltage-clamp and current-clamp protocols. Sevoflurane dose-dependently depressed membrane biophysics and HCN-mediated parameters of neuronal excitability. Respective half-maximal inhibitory and effective concentrations ranged between 0.30 (95% CI, 0.18–0.50) mM and 0.88 (95% CI, 0.40–2.20) mM. We witnessed a pronounced reduction of HCN dependent Ih current amplitude starting at a concentration of 0.45 mM (relative change at -133 mV; 0.45 mM sevoflurane: 0.85 [interquartile range, 0.79–0.92], n = 12, p = 0.011; 1.47 mM sevoflurane: 0.37 [interquartile range, 0.34–0.62], n = 5, p < 0.001) with a half-maximal inhibitory concentration of 0.88 (95% CI, 0.40–2.20) mM. In contrast, effects on voltage dependent channel gating were modest with significant changes only occurring at 1.47 mM (absolute change of half-maximal activation potential; 1.47 mM: -7.2 [interquartile range, -10.3– -5.8] mV, n = 5, p = 0.020). In this study, we demonstrate that sevoflurane inhibits the excitability of thalamocortical relay neurons in a concentration dependent manner within a clinically relevant range. Especially with regard to its effects on native HCN channel function, our findings indicate substance-specific differences in comparison to other anesthetic agents. Considering the importance of HCN channels, the observed effects might mechanistically contribute to the hypnotic properties of sevoflurane.